Plastid caseinolytic protease OsClpR1 regulates chloroplast development and chloroplast RNA editing in rice - Liu, Xi (Rice (N Y), 2021)
BACKGROUND: Plant plastidic caseinolytic protease (Clp) is a central part of the plastid protease network and consists of multiple subunits. The molecular functions of many Clps in plants, especially in crops, are not well known. RESULTS: In this study, we identified an albino lethal mutant al3 in rice, which produces albino leaves and dies at the seedling stage. Molecular cloning revealed that AL3 encodes a plastid caseinolytic protease, OsClpR1, homologous to Arabidopsis ClpR1 and is targeted to the chloroplast. Compared with the wild type, chloroplast structure in the al3 mutant was poorly developed. OsClpR1 was constitutively expressed in all rice tissues, especially in young leaves. The OsClpR1 mutation affected the transcript levels of chlorophyll biosynthesis and chloroplast development-related genes. The RNA editing efficiency of three chloroplast genes (rpl2, ndhB, ndhA) was remarkably reduced in al3. Using a yeast two-hybrid screen, we found that OsClpR1 interacted with OsClpP4, OsClpP5, OsClpP2, and OsClpS1. CONCLUSIONS: Collectively, our results provide novel insights into the function of Clps in rice. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12284-021-00489-6.